Design and construction of a variables quick switching sampling system based on Taguchi capability index. (October 2021) - Wang, Zih-Huei; Wu, Chien-Wei
Highlights: The core findings of the article are listed below. A new type of quick switching sampling system is developed based on Cpm index. An exact form of the system's operating characteristic function is derived. An optimization model is constructed to determine system's parameters. The proposed system's performance is examined and compared with the existing plans. A case study is presented to illustrate the proposed system's applicability. Abstract: Quick switching sampling (QSS) system comprises a pair of single sampling plans with switching rules and has been developed for lot disposition. The traditional QSS system for variables data only focused on products' yield evaluation but ignored the additional loss caused when the quality deviated from the target value. Therefore, the purpose of this research is to develop a variables QSS system based on the loss-based capability index. To determine the designed plan parameters, a nonlinear optimization problem is constructed. The objective function is minimizing the required average sample number, and the constraints are set to satisfy the quality requests and allowable risks demanded by the producers and consumers, simultaneously. The performance of the proposed system is investigated and compared with other existing methods in terms of the operating characteristic, average sample number, and average run length. Finally, a practical case is presented for illustrating the applicability of the proposed plan.